2013
DOI: 10.3109/08039488.2013.844273
|View full text |Cite|
|
Sign up to set email alerts
|

Stalking experiences and associated factors—A controlled population-based study from Norway

Abstract: The prevalence of stalking was within the range observed by questionnaire studies in other cultures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 21 publications
1
16
0
1
Order By: Relevance
“…In our population-based study (Narud et al, 2013), genuine stalking included presence of (a) -(c): (a) at least one positive item on the stalking screening; (b) the stalking experiences happened at least twice a month; and (c) the stalkingrelated traumatic anxiety (IES-6) score was positive. See also Mullen, Pathé, & Purcell (2009).…”
Section: Genuine Stalkingmentioning
confidence: 99%
See 2 more Smart Citations
“…In our population-based study (Narud et al, 2013), genuine stalking included presence of (a) -(c): (a) at least one positive item on the stalking screening; (b) the stalking experiences happened at least twice a month; and (c) the stalkingrelated traumatic anxiety (IES-6) score was positive. See also Mullen, Pathé, & Purcell (2009).…”
Section: Genuine Stalkingmentioning
confidence: 99%
“…The invitation reached 4752 individuals and among them 1520 (32%) returned the questionnaire, but 98 had to be discarded due to lack of completion, giving a sample of 1422 valid questionnaires (30%) (Narud et al, 2013).…”
Section: The General Population Samplementioning
confidence: 99%
See 1 more Smart Citation
“…iii) Physical interference with the individual's personal environment or possessions Physical surveillance/being followed (1); electronic surveillance (5); subject to electronic hacking (8); subject to clandestine, unauthorised entry to home (13); vandalism/theft of property (14); and family and friends also targeted (17). iv) Assault on reputation Targeted by slander/gossip (11). v) Individuals or agencies involved in perpetrating or collaborating with the gang-stalking Police as part of the conspiracy (15); neighbours as part of the conspiracy (16); family/friends as part of the conspiracy (19); producing 'evidence' of gang-stalking fails to persuade authorities to intervene (22); and medical practitioners as part of the conspiracy (23).…”
Section: I)mentioning
confidence: 99%
“…The prevalence in different studies varies according to the definition used, the methodology employed, and the population or sub-population sampled. But even the most conservative estimates suggest that 8% of women and 2% of men are stalked at some point in their lives [6,7], and other studies from a range of western countries have found rates that were twice as high [8][9][10][11][12][13][14][15]. By contrast, indications as to the prevalence of gang-stalking experiences are few in number.…”
Section: Introductionmentioning
confidence: 99%